Strategi Peningkatan Kinerja Bisnis Kuliner melalui Optimalisasi Kualitas Produk dan Kualitas Pelayanan - Uswatun Chasanah; Rahayu Mardikaningsih; Didit Darmawan; Siti Nur Halizah (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
The research aims to analyze strategies to improve the performance of the culinary business through optimization of the quality of products and services in the Micro, Small and Medium Enterprises (UMKM) of the Culinary Industry in the City of Surabaya. The research method used was a quantitative approach involving 90 respondents from the UMKM culinary industry in Surabaya. This research includes an analysis of product quality and service quality as free variables, while business performance as variables. The data collection was carried out through a questionnaire distributed to the owners of culinary UMKM in Surabaya City. Data analysis techniques using double linear regression. The results of data analysis showing that the quality of products and services have a significant impact on the performance of Micro, Small and Medium Enterprises (MSMEs) in the culinary industry in Surabaya City illustrate the importance of these two factors in determining the success of the business. While the quality of service is an important aspect in building good relationships with customers.